Peranan Strategi Promosi Pemasaran Terhadap Peningkatan Volume Penjualan - Amanah, Siti (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2015)
Abstract: The success of company is determined by various factors. One of them is the marketing of products supported by implementing for the appropriate promotion strategy. This marketing promotion strategy has a very important role for the company to especially maintain its existence in the field. It is as an attempt to increase selling of various products. Besides that, the marketing strategy which is set has to be reviewed and developed in coresponding with the development of the market environment. The businesses competition which always increase, deciding the right promotional strategy is essential in order to escalate the selling.